Business models and ICT technologies for the fashion supply chain : proceedings of IT4Fashion 2016 - Rinaldi, Rinaldo; Bandinelli, Romeo (Lecture notes in electrical engineering ;, 2017)
This book presents high-quality original contributions on the fashion supply chain. A wide spectrum of application domains are covered, processing of big data coming from digital and social media channels, fashion new product development, fashion design, fashion marketing and communication strategy, business models and entrepreneurship, e-commerce and omni-channel management, corporate social responsibility, new materials for fashion product, wearable technologies. The contents are based on presentations delivered at IT4Fashion 2016, the 6th International Conference in Business Models and ICT Technologies for the Fashion Supply Chain, which was held in Florence, Italy, in April 2016. This conference series represents a targeted response to the growing need for research that reports and debates supply chain business models and technologies applied to the fashion industry, with the aim of increasing knowledge in the area of product lifecycle management and supply chain management in that industry.